Correlation of Serum Biomarkers and Magnetic Resonance Spectroscopy in Monitoring Disease Progression in Patients With Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke-Like Episodes Due to mtDNA A3243G Mutation - Lee, Ha Neul; Yoon, Choon-Sik; Lee, Young-Mock (Frontiers in Neurology, 2018)
Background: Analysis of serum biomarkers and magnetic resonance spectroscopy (MRS) are useful for monitoring disease progression in patients with mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS). We evaluated the correlation of serum biomarkers and MRS parameters during changes associated with stroke-like episodes. Methods: In 13 symptomatic MELAS patients carrying the A3243G mutation, we retrospectively obtained 207 voxels from 41 MRS studies, which were divided into 3 groups according to the temporal association with stroke-like episodes. The MRS NAA/Cr, Cho/Cr, NAA/Cho ratios, the presence of a lactate peak, serum biomarkers, serum lactate level, and the pyruvate (Lac/Pyr) ratio were determined. Results: In regions with acute infarcts, the severity of serum Lac/Pyr and that of the MRS lactate peak (P = 0.0007) correlated; serum lactate (P = 0.02), severity of elevated serum lactate (P = 0.04), and serum Lac/Pyr (P = 0.02) correlated weakly. In previously infarcted regions, the severity of the MRS lactate peak and serum Lac/Pyr (P = 0.03), as well as the severity of serum Lac/Pyr (P = 0.02) were weakly correlated. In structurally normal regions, we found a weak to moderate negative correlation between serum lactate and MRS NAA/Cr (P = 0.008), and between the severity of elevated serum lactate and MRS NAA/Cr (P = 0.002) as well as MRS NAA/Cho (P = 0.02). Conclusions: MRS parameters correlate with specific serum biomarkers, and are useful for monitoring changes in brain metabolites, particularly as related to stroke-like episodes. Keywords: lactate peak, magnetic resonance spectroscopy (MRS), mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes (MELAS), mitochondrion, pediatric, serum lactate